Analysis of the Application of the Internal Auditor Code of Ethics in the Drama The Auditors Episode 1-4 - Monika Handayani; Fahristi Fatima Az Zahra (Asian Journal of Management, Entrepreneurship and Social Science, 2025)
This study aims to analyze the application of the code of ethics of the internal auditor profession in the drama The Auditors through certain excerpts that illustrate the violation and application of ethical principles in the audit process. The method used is a qualitative analysis by focusing on eight excerpts from various episodes in the drama. The results showed that the characters in the drama often violated some of the basic principles of the internal auditor code of ethics, such as objectivity, confidentiality, and integrity. These violations include accepting gifts from auditees, leaking audit information, concealing audit evidence, and engaging in illegal activities. Despite the violations, other auditors also applied the code of ethics well, such as competence in obtaining audit information and accountability in reporting audit results. This research provides important insights into the ethical challenges faced by internal auditors in carrying out their duties and the importance of understanding and applying the code of ethics to maintain the integrity of the audit profession.